ANALISIS SOAL-SOAL MATEMATIKA TIPE HIGHER ORDER THINKING SKILLS (HOTS) UNTUK MENDUKUNG KEMAMPUAN PENALARAN MATEMATIS SISWA SMP - Putri Rlisya, Inge; Fonna, Mutia; Listiana, Yeni; Muhammad, Iryana; Wulandari, Wulandari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
The ability to think logically and draw conclusions using logic is known as mathematical reasoning. Students understand how to use mathematical reasoning to manipulate formulas and properties, construct proofs, and explain ideas in mathematical statements. Answering HOTS (Higher Order Thinking Skills) questions improves mathematical reasoning. HOTS questions are higher-order thinking skills questions that require a reasoning process to be demonstrated when knowledge and skills are applied in new or more complex contexts. The purpose of this research was to determine the results of an analysis of HOTS type questions that could aid students' mathematical reasoning abilities. This study takes a qualitative approach, with content analysis serving as the descriptive research method. The HOTS type of question was found in 9 of the 40 Madrasah Exam questions examined. HOTS questions are those that assist students in developing their mathematical reasoning skills.Keywords: Mathematical Reasoning Ability, HOTS Type Questions, Madrasah Exam Questions.